The Hello Girls : America's first women soldiers - Cobbs, Elizabeth (Harvard University Press, 2017)
"In World War I, telephones linked commanding generals with soldiers in muddy trenches. A woman in uniform connected almost every one of their calls, speeding the orders that won the war. Like other soldiers, the "Hello Girls" swore the Army oath and stayed for the duration. A few were graduates of elite colleges. Most were ordinary, enterprising young women motivated by patriotism and adventure, eager to test their mettle and save the world. The first contingent arrived in France just as the German Army trained "Big Bertha" on Paris, bombarding the frightened city as the new women of the U.S. Army struggled through unlit streets to find their billets. A handful followed General Pershing to the gates of Verdun and the battlefields of Meuse-Argonne. When the switchboard operators sailed home a year later, the Army dismissed them without veterans' benefits or victory medals. The women commenced a sixty-year fight that a handful of survivors carried to triumph in 1979. This book shows how technological developments encouraged an unusual band to volunteer for military service at the precise moment that feminists back home championed a federal suffrage amendment. The same desire to participate fully in the life of their country animated both groups, and both struggled after 1920 to reap the rewards of victory. Their experiences illuminate ways in which sex-role change was embraced and resisted throughout the twentieth century, and the ways that men and women struggled together for gender justice."--Provided by publisher.